Improving Junior High School Students' Speaking Skills through Role-Play and Peer Feedback - Aji, Henggar Prasetyo; Irawan, Rifki (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
Through role-play and peer feedback, this research aims to improve students' English-speaking skills in Grade VIII of junior high school in Wangon, Central Java. It used Classroom Action Research (CAR) based on Kemmis and Mc Taggart's design to solve the students' problems with English Speaking. The researcher did two cycles: planning, acting, observing, and reflecting. Qualitative and quantitative data were gathered from interview and observation results and speaking scores. The finding of this study indicated that the implementation of the role-play and peer feedback technique was successful since the success criteria were achieved. The first criterion was that 50% of students could pass the target score ≥ 70 based on the KKM. The finding showed that 48.15% of students had already achieved the target score. Besides, the second criterion was the students who become more actively involved in the teaching-learning process. The result of observation and interview showed that by using role play and peer feedback techniques, students were actively involved in the classroom activity. Based on the previous finding, the writer suggests that the English teacher could implement Role play and peer feedback techniques in teaching speaking to improve students' English-speaking skills.